2004
DOI: 10.1016/j.apradiso.2004.05.073
|View full text |Cite
|
Sign up to set email alerts
|

Application of GEANT4radiation transport toolkit to dose calculations in anthropomorphic phantoms

Abstract: In this paper we present the implementation of a dose calculation application, based on the GEANT4 Monte Carlo toolkit. Validation studies were performed with an homogeneous water phantom and an Alderson-Rando anthropomorphic phantom both irradiated with high-energy photon beams produced by a clinical linear accelerator. As input, this tool requires computer tomography images for automatic codification of voxel based geometries and phase space distributions to characterize the incident radiation field. Simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In addition, there exists limited long-term secondary toxicity data for proton therapy, as presented in several institutional case-series. Much of the supporting evidence for protons is derived from theoretical comparative dosimetric models, with SMN risk assessment by various measurement techniques or Monte Carlo calculations, using generic or anthropomorphic phantom models, and with different source data for risk modeling (Chaves et al, 2004; Rodrigues et al, 2004; Fontenot et al, 2009; Taddei et al, 2009). The effects of fractionation and dose-rate are also not generally considered (Jones, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there exists limited long-term secondary toxicity data for proton therapy, as presented in several institutional case-series. Much of the supporting evidence for protons is derived from theoretical comparative dosimetric models, with SMN risk assessment by various measurement techniques or Monte Carlo calculations, using generic or anthropomorphic phantom models, and with different source data for risk modeling (Chaves et al, 2004; Rodrigues et al, 2004; Fontenot et al, 2009; Taddei et al, 2009). The effects of fractionation and dose-rate are also not generally considered (Jones, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…However, study focusing on fluoroscopy has not been found yet. Previous researches were concerned about the impact of scattered radiation on patient dose [10,11,14,16,17] and radiographic image quality [14,18,19] , and the physical properties of radiation [12,20] , but there has not been study on the occupational dose of radiology department staff. Besides, the results obtained in general X-ray study cannot represent validly in fluoroscopy because the properties of these two modalities are different.…”
Section: Clinical Applications Of Fluoroscopy and Its Radiation Dosementioning
confidence: 99%
“…The knowledge on the nature and geometric patterns of scattered radiation has long been inadequate and researchers have proposed different methods to identify the scattering properties based on different radiation sources. General X-ray machines, computed tomography and radionuclide imaging have been considered as the main foci in radiology studies [10][11][12][13][14][15] . However, study focusing on fluoroscopy has not been found yet.…”
Section: Clinical Applications Of Fluoroscopy and Its Radiation Dosementioning
confidence: 99%
“…The Monte Carlo codes in literature are mainly EGS (Malataras 1996;Ayyangar 1998;Leal 2003;Reynaert 2004), MCNP (Moraleda 2004) and GEANT (Trindade 2003;Rodrigues 2004) for radiotherapy studies.…”
Section: Dose Deposition Calculationsmentioning
confidence: 99%